Going beyond "it depends:" the role of context in shaping participation in natural resource management - Baker, Susan; Chapin III, F. Stuart (Ecology and society, 2018)
Public participation is increasingly advocated in natural resource management to meet a spectrum of instrumental to normative goals. However, the success of participation in achieving these goals is highly variable, depending on both societal and institutional contexts. Whether participation realises its benefits or succumbs to its pitfalls is shaped by dynamic interactions operating among three contextual dimensions: participatory rationales (instrumental to normative), institutional fit of different levels (types) of participation (information delivery to partnership to delegation), and social structures (such as cultural context, social capital, and power distribution). Some levels of participation may support the existing power hierarchy, others benefit organized stakeholder groups and special interests, and still others foster deliberative democratic outcomes. We argue that wise choice of levels of participation in particular contexts shapes the balance of participation’s benefits and pitfalls.